Diagnostic Value of Interferon-Gamma Release Assays Combined with Multiple Indicators for Tuberculous Peritonitis - Xidong He; Yuanxue Gao; Qi Liu; Zhifang Zhao; Wanhang Deng; Hong Yang (Gastroenterology Research and Practice)
Objective. To investigate the diagnostic value of interferon-gamma release assays combined with multiple indicators for tuberculous peritonitis. Methods. Patients who were admitted to the hospital due to suspected tuberculous peritonitis were prospectively included during the 30-month study period. Moreover, healthy individuals were recruited and included in the control group. All the study participants were assessed using various indexes, such as interferon-gamma release assays. Results. A total of 180 patients with suspected tuberculous peritonitis were enrolled, and 24 were excluded. 73 patients with a confirmed diagnosis of tuberculous peritonitis were included in the tuberculous peritonitis group, 83 patients with other diseases in the other-disease control group, and 52 healthy individuals in the control group. Moreover, 83 patients in the other-disease control group and 52 participants in the control group were identified as 135 nontuberculous peritonitis patients. The area under the receiver operating characteristics curve for the QuantiFERON-TB test was 0.851 (95% confidence interval: 0.799–0.903), and the optimal cutoff value was 0.55 IU/mL, which corresponds to a sensitivity and specificity of 86.30% and 80.00%, respectively. The receiver operating characteristic curves for the combination of the QuantiFERON-TB test and the use of erythrocyte sedimentation rate, serum adenosine deaminase level, serum cancer antigen 125 level, and hypersensitive C-reactive protein level had an area under the curve of 0.859 (95% confidence interval: 0.809–0.909), with a sensitivity and specificity of 97.26% and 62.96%, respectively. Conclusions. The combined use of the QuantiFERON-TB test and multiple indexes can significantly improve the accuracy of diagnosing tuberculous peritonitis.